1981
DOI: 10.1111/j.1651-2227.1981.tb06233.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cytomegalovirus Infection in Nurses and Congenital Infection in Their Offspring

Abstract: The risk of contracting cytomegalovirus (CMV) infection in nursing of infants and of congenital CMV infection in infants born to such nursing personnel were investigated. The investigation comprised 292 women working in paediatric clinics or day nurseries and a control group of 163 women who had no professional contact with infants. Among the women younger than 25, those who had tended infants for more than six months were significantly (p less than 0.001) more often seropositive for CMV than were those--mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Then they showed that after exposure to infected babies for 2 years, the attack rates of CMV infection in the health care worker were not higher than the control population in the community. Similar results were found in Sweden (Ahlfors et al, 1981b). Balfour and Balfour (1986) enrolled four study groups, i.e., transplant or hemorlialysis nurses, 204 neonatal intensive care nurses, 225 student nurses, and 251 blood donor controls, in an even moreextensive prospective study.…”
Section: Other Mechanisms Of Transmission and Transmission In The Wosupporting
confidence: 65%
“…Then they showed that after exposure to infected babies for 2 years, the attack rates of CMV infection in the health care worker were not higher than the control population in the community. Similar results were found in Sweden (Ahlfors et al, 1981b). Balfour and Balfour (1986) enrolled four study groups, i.e., transplant or hemorlialysis nurses, 204 neonatal intensive care nurses, 225 student nurses, and 251 blood donor controls, in an even moreextensive prospective study.…”
Section: Other Mechanisms Of Transmission and Transmission In The Wosupporting
confidence: 65%
“…CMV seroprevalence in the underlying population did not appear to be a predictor of the rate of seroconversion ( Figure 2B). Risk factors for seroconversion were only reported in a few studies, and included patient contact [21], contact with children [22] and extended contact with infants [23].…”
Section: Results In Healthcare Workersmentioning
confidence: 99%
“…The study above found that, when the CMV isolate obtained from the one nurse found to acquire infection during the study were compared with isolates from 34 out of the 35 babies, no two isolates were the same 16. Other epidemiological studies have found that, in studies of women working in paediatric clinics or day nurseries, there is no difference in CMV antibody seropositivity compared with women whose occupations did not involve direct care of infants 17 18. More importantly, when occupations of the mothers in 36 cases of congenital CMV were studied, there was no over-representation of nurses 17…”
Section: Epidemiologymentioning
confidence: 93%